Pengaruh Media Sosial Sebagai Sarana Edukasi Kesehatan Mental Remaja - Susilawati, Susilawati; Yanti, Lussyefrida; Fredrika, Larra (Poltekkes Kemenkes Bengkulu, 2025)
Social media has become an integral part of adolescents' daily lives and is regarded as a crucial aspect of their social environment. Due to its pervasive use, social media holds great potential as an educational platform, particularly for increasing awareness and knowledge of mental health. Mental health literacy among adolescents is essential to enable early detection of psychological problems and encourage timely help-seeking behavior. This study aimed to examine the effect of social media as an educational tool on improving adolescents’ knowledge of mental health. A quasi-experimental design with a one-group pretest-posttest approach was employed, involving 30 adolescent participants selected through purposive sampling. The intervention consisted of educational content on mental health delivered over 14 days via WhatsApp, TikTok and Instagram. A structured knowledge questionnaire was administered before and after the intervention to measure changes in understanding. Data analysis using paired sample t-test revealed a significant increase in participants’ knowledge scores from a pretest mean of 63.3 to a posttest mean of 82.7 (p = 0.000). The results suggest that mental health education delivered through social media is effective in enhancing adolescents' knowledge. Therefore, social media can serve as a strategic, accessible, and engaging platform for mental health education and promotion targeted at youth. Keywords: social media, education, mental health, adolescents